Contact morphology and revisited photocurrent dynamics in monolayer MoS2. (December 2017) - Parzinger, Eric; Hetzl, Martin; Wurstbauer, Ursula; Holleitner, Alexander
Abstract Two-dimensional (2D) layered transition metal dichalcogenides (TMDs) have emerged as promising materials for electronic, optoelectronic, and valleytronic applications. Recent work suggests drastic changes of the band gap and exciton binding energies of photo-excited TMDs with ultrafast non-radiative relaxation processes effectively heating the crystal lattice. Such phenomena have not been considered in the context of optoelectronic devices yet. We resolve corresponding ultrafast photoconductance dynamics within monolayer MoS2 . The data suggest that a bolometric contribution as well as a defect-related conductance dominate the overall photoconductance. We further reveal that a focused laser illumination, as is used in many standard optoelectronic measurements of MoS2, can modify and anneal the morphology of metal contacts. We show that a junction evolves with lateral built-in electric fields, although Raman spectra and photoluminescence spectra indicate no significant changes, such as a crystal phase transition. We highlight how such optimized devices can drive ultrafast electromagnetic signals in on-chip high-frequency and THz circuits. Optoelectronics: ultrafast spectroscopy unveil the photoconductance dynamics in MoS2 The interplay between bolometric response and defect-related conductance effects in monolayer MoS2 is unveiled by spectroscopic techniques. A team led by Alexander Holleitner at the Technical University of Munich performed both continuous wave and ultrafast spectroscopy to identify the key contributions to the MoS2 ultrafast photoconductance dynamics. Scanning photocurrent experiments performed on a variety of samples in presence of a focused laser spot tracked the effects of contact annealing in metal/MoS2 /metal devices, and showed that the former results in a permanent renormalization of the contact energy landscape. In turn, the built-in electric fields at the annealed contact promote a bolometric response in combination with defect-related conductance effects, which dominate the optoelectronic signal. These observations contribute to a better understanding of optoelectronic experiments on 2D materials that make use of a focused laser spot.